2008
DOI: 10.1103/physrevb.77.165110
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced local moments around nonmagnetic impurities in metallic cuprates

Abstract: We consider a defect in a strongly correlated host metal and discuss, within a slave-boson mean field formalism for the t-tЈ-J model, the formation of an induced paramagnetic moment which is extended over nearby sites. We study in particular an impurity in a metallic band, suitable for modeling the optimally doped cuprates, in a regime where the impurity moment is paramagnetic. The form of the local susceptibility as a function of temperature and doping is found to agree well with recent NMR experiments, witho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…(1)(b)) in an almost-localized host. A somewhat similar result emerges in the t−t ′ −J model, in which an impurity induces a local staggered magnetization in its vicinity [17,18] whose spatial extent also increases with correlations. The critical behavior of δZ i is captured by our analytical expressions and we can show that, for d ≥ 2, and r io /ξ ≫ 1…”
supporting
confidence: 60%
“…(1)(b)) in an almost-localized host. A somewhat similar result emerges in the t−t ′ −J model, in which an impurity induces a local staggered magnetization in its vicinity [17,18] whose spatial extent also increases with correlations. The critical behavior of δZ i is captured by our analytical expressions and we can show that, for d ≥ 2, and r io /ξ ≫ 1…”
supporting
confidence: 60%
“…To compensate it, Wang and Lee added a phenomenological residual spin-spin interaction term, and the result depends on its magnitude. In addition, Gabay et al 20 recently obtained similar results. Liang and Lee 21 applied the VMC and also concluded that local moments appear in the underdoped regime.…”
Section: Introductionmentioning
confidence: 63%
“…From the theoretical side, we have included strong electronic correlations only in a very phenomenological way, by introducing local suppressions of the hole mobility around the impurity site, as found by more sophisticated treatments in the normal state. 39 As these effects appear to be important, theoretical treatments of impurities in the superconducting state capable of treating inhomogeneous order parameter situations together with strong correlations are clearly desirable. On the experimental side, we have discussed ways in which improving statistics on impurity resonances and how they are defined could provide important insights, and proposed various tests of the scenarios treated here which should enable one to distinguish them.…”
Section: Discussionmentioning
confidence: 99%